The Double Life of Doxography - Maitra, Nabanjan (JAOS, 2025)
Building on the recent interest in doxographic texts in the study of Indian philosophy, this article tackles one of the foundational claims regarding the structure of Advaita Vedānta doxographies, namely, their essentially hierarchical character, by examining the fourteenth-century Sarvadarśanasaṃgraha, one of its most celebrated examples. Contesting the long-standing scholarly consensus that the Sarvadarśanasaṃgraha’s arrangement of the views it catalogues discloses Advaita Vedānta’s tendency to hierarchize as a means to asserting its doctrinal supremacy, the article argues that the partially hierarchical structure of the Sarvadarśanasaṃgraha may be better explained by considering the intellectual and institutional contexts of the text’s composition. Detailing the text’s connections to the massive scholastic enterprise undertaken by the Śṛṅgeri monastery (maṭha) in the fourteenth century, the article demonstrates that the structure of the text conforms to the brand of Vedic authority expressed in this commentarial corpus. Through its arrangement of the philosophical views it describes, the Sarvadarśanasaṃgraha divides up the śāstric universe into four domains, the anti- Vedic, the non-Vedic Vaiṣṇava, the non-Vedic Śaiva, and the Vedic. The reasons for this arrangement are neither directly articulated nor argued for by the text itself but may be discerned by examining the wider context of the text’s composition.